Television in the Formation of Civil Society: The Role of a Non- Controversial Public Space in Hong Kong - Lee, Paul S. N. (Television, Regulation and Civil Society in Asia, 2002)
Television first appeared in Hong Kong in 1957. It was a cable television service run by the Rediffusion Company which had operated a highly successful wired sound broadcasting service since 1949. Hong Kong was the first British colony to have television. But the Rediffusion television service was very expensive. Its monthly subscription fee was HK$55. In 1958, a technical worker’s monthly wages were HK$360 and an unskilled worker earned only HK$75 (Hong Kong Government 1959: 32). A year before the introduction of free-to-air television in 1967, Rediffusion television had only 67,000 subscribers (Hong Kong Government 1967: 206). Thus before 1967 television was an elite medium and its social impact was minimal.
Num Pages: 8
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé